2023
DOI: 10.3390/jcm12082807
|View full text |Cite
|
Sign up to set email alerts
|

Living-Donor Liver Transplant and Improved Post-Transplant Survival in Patients with Primary Sclerosing Cholangitis

Abstract: Primary sclerosing cholangitis (PSC) is the leading indication of liver transplantation (LT) among autoimmune liver disease patients. There is a scarcity of studies comparing survival outcomes between living-donor liver transplants (LDLT)s and deceased-donor liver transplants (DDLTs) in this population. Using the United Network for Organ Sharing database, we compared 4679 DDLTs and 805 LDLTs. Our outcome of interest was post-LT patient survival and post-LT graft survival. A stepwise multivariate analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We found that the presence of ascites, hepatic encephalopathy, and the need for dialysis were all significantly less common in patients who underwent LDLT compared to those of patients who underwent DDLT. Similarly, another study reported that patients with primary sclerosing cholangitis who underwent LDLT less commonly had ascites and hepatic encephalopathy compared to those whose underwent DDLT, although this study was not conducted in patients with ALF [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the presence of ascites, hepatic encephalopathy, and the need for dialysis were all significantly less common in patients who underwent LDLT compared to those of patients who underwent DDLT. Similarly, another study reported that patients with primary sclerosing cholangitis who underwent LDLT less commonly had ascites and hepatic encephalopathy compared to those whose underwent DDLT, although this study was not conducted in patients with ALF [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we opted to further stratify DDLT into distinct categories, namely DBD and DCD, a comparison that has only been explored in one other study [19]. However, it is important to note that this comparison study encompassed including another cholestatic liver disease such as PSC, which has a distinct underlying pathogenesis, prognosis, and course of disease after LT [28]. With the implementation of the MELD 3.0, which introduces adjustments to the MELD score, particularly including female sex, we anticipated changes in the waiting list outcomes and post-LT outcomes after DDLT or LDLT in PBC recipients in the subsequent years [29].…”
Section: Discussionmentioning
confidence: 99%
“…Within this series, 55 out of 805 LDLT cases culminated in an iCC diagnosis, with an overall survival rate for LDLT recipients reaching 81.9%. Intriguingly, multivariate analysis identified concurrent cholangiocarcinoma as a significant predictor of mortality (HR: 2.07; 95% CI: 1.71–2.50; p < 0.001) ( 31 ). The second largest series was published in 2020 by Bhatti et al., who analyzed the experience in LDLT for cholangiocarcinoma in cases with early stages of the disease and incidental diagnoses.…”
Section: Ldlt For Iccmentioning
confidence: 99%